Upaya Peningkatan Motivasi Belajar Siswa Kelas 4 Materi PAK Melalui Metode Problem Based Learning (PBL) di SD Negeri 25 Gonis Rabu - Cornellya Nelly (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This classroom action research was motivated by students' low learning motivation. Based on the data presented, there were 10 students in class 4. 4 students achieved scores above the completeness criteria, and 6 students obtained scores below the completeness criteria. set. This data shows that students' understanding of the material I Am a Unique Personality is still low. As a formulation of the problem in this research, is the PBL method of learning Catholic Religion able to increase the learning motivation of grade 4 students at SD Negeri 25 GonisRabu, Sekadau Hilir District, Sekadau Regency. The aim of this research is to increase the learning motivation of grade 4 students at SD Negeri 25 Gonis Rabu. This research uses the PBL method. Education is a conscious effort to develop all aspects of human life which include knowledge, values ​​and attitudes as well as skills. Within the SD Negeri 25 Gonis Rabu environment, efforts are made for students to develop optimally both in terms of intellectual and personality... However, in reality, Catholic Religious Education is sometimes lacking. attention from students. This is because the methods used by teachers and also the lack of facilities used to convey the material make students bored. Learning motivation is the overall driving force within students that gives rise to learning activities, which ensures the continuity of learning activities that provide direction so that the desired goals can be achieved. The objectives of the research include (1) to find out how the use of the Problem Based Learning model in increasing students' learning motivation on unique personal material as equals for men and women in class IV SD Negeri 25 Gonis Rabu, (2) to find out the increase in learning motivation fourth grade students at SD Negeri 25 Gonis Rabu with the help of the Problem Based Learning model on unique personal material as equal men and women, (3) to find out the use of the Problem Based Learning model on unique personal material as equal men. and female, fourth grade students at SD Negeri 25 Gonis Rabu can apply the Pancasila student profile of the independence dimension. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation, interviews and documentation. The data analysis technique used consists of data reduction by selecting raw data to be used as information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results referring to the problem formulation. The use of the Problem Based Learning model according to syntax which includes student orientation towards problems, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem solving process, effectively helps increase learning motivation and student independence in unique personal material as equal boys and girls in class IV of SD Negeri 25 Gonis Rabu.